Dietary effect of low fish meal aquafeed on gut microbiota in olive flounder (Paralichthys olivaceus) at different growth stages - Kai‐Min Niu; Bong‐Joo Lee; Damini Kothari; Woo‐Do Lee; Sang‐Woo Hur; Sang‐Gu Lim; Kang‐Woong Kim; Kyoung‐Duck Kim; Na‐Na Kim; Soo‐Ki Kim (MicrobiologyOpen, 2020)
Abstract This study was conducted to investigate the long‐term effect of a low fish meal (FM) diet comprising plant‐based protein sources (PPS) on changes of gut microbial diversity in olive flounder (Paralichthys olivaceus) over the course of life. Two experimental diets were prepared to contain 74% FM (control) or 52% FM with 22% PPS (30% FM replacement, FM30). Fish were fed one of the two experimental diets for 8 months, and we collected the midgut contents to analyze the gut bacterial community by Illumina MiSeq based on the metagenomic sequences in the V3–V4 regions of 16S rRNA. We found that there were nine dominant phyla, which in turn presented Proteobacteria, Firmicutes, and Actinobacteria as the three major phyla in the gut microbiota of the flounder. At genus level, the dominant genera were Delftia, Prevotella, and Chthoniobacter at the juvenile stage (below 100 g/fish); Chthoniobacter, Bacillus, and Bradyrhizobium at the grower stage (400 g/fish); Chthoniobacter, Bacillus, and Delftia at the subadult stage (800 g/fish); and Lactobacillus and Prevotella at the adult stage (over 1,000 g/fish). The microbial diversity in olive flounders arched from the juvenile and subadult stage and reached a plateau thereafter. The fish fed the FM30 diet significantly had an increased abundance of Lactobacillus and Photobacterium and had less abundance of Prevotella and Paraprevotella than the control. However, the effect of dietary PPS was not significant on total microbial richness, indicating no negative effect as feed sources on the intestinal microbiota in olive flounder. These results indicate that the life stage of olive flounder is more important in modulating intestinal microbiota than is the diet. It could also be concluded that dietary PPS might be used as a potential fish meal alternative without any compromising effects on microbial diversity of olive flounder for long‐term feeding.